Impact of Community-Based Educational Package (CBEP) on Coping Strategies Among Postmenopausal Women - Kaur, Rajinder; Malhotra, Reetu; Chopra, Shivani (Scripta Medica, 2025)
Background/Aim: Menopause is a significant challenge for women’s psychological and physical well-being. Aim of this study was to examine the impact of a 60-minute community-based educational package (CBEP) designed to enhance coping strategies among postmenopausal women in rural Punjab. Methods: A randomised controlled trial with 200 participants (Control: n = 100; Experimental: n = 100) utilised the modified postmenopausal coping scale (PMCS)—a 55-item tool assessing nine domains, including hot flushes, psychological changes, sleep disturbances and sexual dysfunction—to evaluate coping strategies pre- and post-intervention. Results: Baseline assessments revealed significant disparities: 60.8 % of the control group exhibited poor coping knowledge compared to 39.2 % in the experimental group (χ² = 9.684, p = 0.002). Post-intervention, the experimental group demonstrated a marked increase, with poor coping knowledge decreasing to 8.8 % and average coping knowledge rising to 66.4 %, while the control group remained stagnant (91.2 % low knowledge; χ² = 54.202, p = 0.0001). Quantitative analysis further showed significant post-intervention gains in coping scores for the experimental group (mean = 24.92 vs Control: 17.84; t = 13.311, p = 0.0001), with a mean score increase of 6.55 compared to the control group’s 0.36 (t = 17.563, p = 0.0001). Conclusion: Although neither group achieved “good” knowledge levels, the experimental cohort’s shift from poor to average coping strategies underscores the intervention’s effectiveness. These results highlight the value of structured, community-driven educational programs in empowering postmenopausal women to manage menopausal challenges, ultimately enhancing their quality of life.